2017
DOI: 10.1016/j.jtho.2016.11.1890
|View full text |Cite
|
Sign up to set email alerts
|

P3.02c-094 Italian Nivolumab Advanced Squamous NSCLC Expanded Access Program: Efficacy and Safety in Patients with Brain Metastases

Abstract: counts less than 50Â10 9 /L[Median (95%CI): 4.0 (3.0-5.0) days vs. 4.5 (3.0-9.0) days, P>0.05], time of platelet count recovered to 75Â10 9 /L [Median (95% CI): 5(3-7) days vs. 6 (4-8) days, P>0.05] and to 100Â10 9 /L[median (95% CI): 6(6-8) days vs. 6 (5-9) days, P>0.05]. Drug-related adverse events in rhTPO arm were less than those of rhIL-11 arm (5 cases (6.49%) in rhTPO arm, 8 cases (25.8%) in rhIL-11 arm, P<0.05). Conclusion: Although there is no statistical difference on efficacies, prophylactic administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…(none of the PD-L1-negative patients responded in this trial), 18 and is slightly higher than that reported in retrospective series. 20,23,26 Furthermore, patients with BMs progressed more often in the brain than did patients without preexisting BMs. As severe neurological symptoms can develop in these patients because of their brain progression, careful monitoring, especially of active BM, during the first months of ICI treatment seems needed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(none of the PD-L1-negative patients responded in this trial), 18 and is slightly higher than that reported in retrospective series. 20,23,26 Furthermore, patients with BMs progressed more often in the brain than did patients without preexisting BMs. As severe neurological symptoms can develop in these patients because of their brain progression, careful monitoring, especially of active BM, during the first months of ICI treatment seems needed.…”
Section: Discussionmentioning
confidence: 95%
“…Available series on patients with BMs treated with an ICI in daily practice mainly come from expanded access programs (EAPs) or from small retrospective series. [19][20][21][22][23][24][25][26][27] The EAP cohorts have the same biases as the randomized trials, as they generally required BMs to be treated, stable, and asymptomatic. 23,24 As a result, many questions, such as the prognostic value of the disease-specific Graded Prognostic Assessment (ds-GPA) classification (Supplementary Table 1) 28 or the optimal timing of cranial irradiation, remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that high titers against SSA/Ro were already present in serum samples taken before the start of anti-PD1 treatment [20]. Another important report on nivolumab for the treatment of CNS metastases was the Italian EAP for advanced squamous NSCLC [21]. Of 372 patients, 38 with asymptomatic brain metastases received nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS and OS were 5.5 and 6.5 months, respectively. Only one of the 38 BM patients discontinued treatment due to AEs [66].…”
Section: Nivolumab Seriesmentioning
confidence: 99%